IL-21 does not involve in OVA-induced airway remodeling and chronic airway inflammation - Chen, Huilong (Int J Clin Exp Med, 2015)
Interleukin (IL-21) is a member of the type I cytokine family with sequence homology to IL-2, IL-4, and IL-15. IL-21 has been reported to improve symptoms of allergic rhinitis in mice. In this study we examined whether IL-21 signaling involved in allergic airway inflammation and remodeling in vivo by using ovalbumin (OVA)-induced chronic asthma model. We showed IL-21 level was increased in the serum of asthma models but not bronchoalveolar lavage fluid (BALF). Intranasal administration with recombinant mouse IL-21 or anti-IL-21 receptor (IL-21R) antibody did not affect OVA-induced chronic airway inflammation and airway remodeling in vivo and also not affect the expression of IL-13 and TGF-β in BALF. Moreover, expression of IL-13 and TGF-β was not affect by intranasal administration with recombinant mouse IL-21 or anti-IL-21R antibody. These results indicated that IL-21 signaling might not play an important role in airway inflammation and remodeling.